Postmodern investment: facts and fallacies of growing wealth in a multi-asset world - Crowder, Garry B; Schneeweis, Thomas; Kazemi, Hossein (Wiley finance series, 2013)
Written by an all-star team of investment management experts, this book debunks common myths and misconceptions about most classes of alternative investments and offers valuable advice on how to develop investment management and asset allocation strategies consistent with the new realities of the ever-changing world of alternative investments.